Osteoclast-derived exosomal miR-214-3p inhibits osteoblastic bone formation - Defang Li (Nature Portfolio, 2016)
In previous studies the authors discovered that miR-214 inhibits osteoblastic bone formation. Here they extend on these findings, using ovariectomized mice and samples from patients with bone fractures, to show that miR-214 is a mediator of osteoclast-osteoblast crosstalk.